Effects of commonly used nitrification inhibitors—dicyandiamide (DCD), 3,4-dimethylpyrazole phosphate (DMPP), and nitrapyrin—on soil nitrogen dynamics and nitrifiers in three typical paddy soils - Zhou, Xue; Wang, Shuwei; Ma, Shutan; Zheng, Xinkun; Wang, Zhiyuan; Lu, Chunhui (Geoderma, 2020)
[Display omitted] •NIs effectively inhibited N2O emission and AOB growth.•NIs could not inhibit AOA growth and nitrification process.•DCD and DMPP were able to inhibit the activity of comammox.•The efficacy of NIs was influenced by soil properties. The use of nitrification inhibitors (NIs) with ammonium (NH4+) -based fertilizers is an efficient strategy for reducing nitrogen (N) loss by affecting ammonia-oxidizing archaea (AOA) and ammonia-oxidizing bacteria (AOB) in agricultural soils. The inhibition mechanisms of NIs on AOA and AOB are still debated, as some studies have demonstrated that NIs inhibited functionally dominant groups, while others have reported selective inhibition of AOB rather than AOA. Here, we identified the impacts of the most commonly used NIs (dicyandiamide (DCD), 3,4-dimethylpyrazole phosphate (DMPP) and nitrapyrin) on the nitrification activity, N2O emission, and abundance and metabolic activity of ammonia oxidizers (AOA, AOB, and comammox (detected only in HL)) in three paddy soils (HL, JX, and SC) with distinct properties using microcosm incubation combined with the 13CO2-DNA-stable isotope probing (SIP) technique. Most of the NIs treatments effectively inhibited the N2O emission with efficacy suppressed the metabolic activity of AOB, regardless of soil type and NI type, whereas the nitrification process and AOA activity could not be inhibited. The efficacy of NIs was also dependent on soil chemical properties, as nitrapyrin did not inhibit AOB growth at the beginning of microcosm incubation in HL, and DCD successfully inhibited the activity of both AOA and AOB in JX. In HL, DCD and DMPP effectively inhibited the activity of comammox, while nitrapyrin could not inhibit its activity. This study is the first to identify the response pattern of comammox to DCD, DMPP, and nitrapyrin in paddy soil by DNA-SIP microcosm incubation. This study also suggested that NIs might selectively inhibit AOB rather than AOA.